The factors that influence entrepreneurial intention among student UiTM Campus Bandaraya Melaka / Nurul Asnida Zainuddin - Zainuddin, Nurul Asnida (Faculty of Business and Management, 2020)
The main purpose of this paper is to examine personality, government support and entrepreneur education might influence entrepreneurial intention among student UiTM Campus Bandaraya Melaka. Specifically, the purpose of the paper is twofold. Firstly, what is the relationship between personality and entrepreneurial intention among student UiTM Campus Bandaraya Melaka. Second, are what is the relationship between government support and entrepreneurial intention among student UiTM Campus Bandaraya Melaka and lastly what is the relationship between entrepreneur education and entrepreneurial intention among student UiTM Campus Bandaraya Melaka. This study is use questionnaire to get the data. This paper provides a comprehensive framework that contributes to the conceptualization of entrepreneur intention and will help practitioners as well as academics to understand what factors can increase entrepreneurial intention among student university.